Call for Action: Agriculture, Landscapes and Livelihoods - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Bruce Campbell, Director at the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) speaks about the negotiation process at COP18 and "the Doha Declaration", which is a step forward in terms of national interests and showing a way forward for agriculture. Video by Meerim Shakirova, social media reporter